2020
DOI: 10.1017/ice.2020.12
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an electronic medical record nudge on reducing testing for hospital-onset Clostridioides difficile infection

Abstract: Objective:To determine the effect of an electronic medical record (EMR) nudge at reducing total and inappropriate orders testing for hospital-onset Clostridioides difficile infection (HO-CDI).Design:An interrupted time series analysis of HO-CDI orders 2 years before and 2 years after the implementation of an EMR intervention designed to reduce inappropriate HO-CDI testing. Orders for C. difficile testing were considered inappropriate if the patient had received a laxative or stool softener in the previous 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In 2020, ASPs continued to publish results of efforts to reduce inappropriate testing for CDI. Howard-Anderson et al described an EMR intervention that prompted a warning screen for prescribers to cancel CDI tests when test orders were placed for patients admitted >3 days who had received laxatives or stool softeners in the prior 24 hours [ 24 ]. Prescribers were able to continue with the order if they selected a button to proceed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, ASPs continued to publish results of efforts to reduce inappropriate testing for CDI. Howard-Anderson et al described an EMR intervention that prompted a warning screen for prescribers to cancel CDI tests when test orders were placed for patients admitted >3 days who had received laxatives or stool softeners in the prior 24 hours [ 24 ]. Prescribers were able to continue with the order if they selected a button to proceed.…”
Section: Resultsmentioning
confidence: 99%
“…Second, many successful ASP interventions incorporate diagnostic stewardship. This year’s baker’s dozen included diagnostic interventions using electronic decision support to decrease ordering of UCs and CDI testing, and rapid diagnostic technology for treating the sickest patient populations [ 9 , 18 , 24 ]. ASPs can examine all steps in the diagnostic process for opportunities to improve patients’ management.…”
Section: Discussionmentioning
confidence: 99%
“…These interventions likely had a much larger impact on HO-CDI rates than our stewardship intervention. [26][27][28] However, they would not explain the change in PD-CDI observed after the stewardship intervention that occurred late in the study period, so that is likely the most critical finding. Our systemwide intervention using electronic order sets with built-in decision support reduced inpatient FQ use by 21% beyond an ongoing drop in month-to-month FQ use that preceded the intervention.…”
Section: Discussionmentioning
confidence: 97%
“…A recent systematic review of 15 studies, evaluating 20 different intervention studies found that 20% of the interventions did not work [ 25 ]. Nudges are designed to non-coercively influence behaviour without forbidding options [ 26 , 27 , 28 , 29 ], and it is the clinicians who must interpret and act. Four potential reasons why our nudges did not change prescribing are explored here.…”
Section: Discussionmentioning
confidence: 99%